The Osteocutaneous Fibular Flap for Mandibular Replacement—Which Factors Influence Long-Term Success? - Kolk, Andreas; Haidari, S.; Wolff, K.-D.; Fichter, A. M.; Kehl, V.; Götz, C.; Kesting, M. R.; Weitz, J. (Journal of Reconstructive Microsurgery Open, 2017)
Background The free fibular flap (FFF) is established for mandibular reconstruction. Some complications, such as non-union, fistulas, and complete graft loss, are sometimes unavoidable. There are no clinically relevant data regarding the optimum selection of osteosynthesis and risk analysis prior to reconstruction.Methods Eighty-three FFFs with up to four osteotomies were analyzed for possible complications during the course of a longitudinal analysis. Forty-one patients underwent simultaneous mandibular reconstruction after tumor resection, and another 42 subjects received FFFs due to infected osteoradionecrosis (ORN). Patients who experienced transplant losses due to vascular occlusion in the grafts were excluded from the study.Results The most common complications were fistulas, bony non-union, and failure of osteosynthesis material. Major contributing risk factors were radiotherapy (p = 0.004), number of osteosynthesis plates >6 (p = 0.002), length of the harvested fibula (p = 0.027), the size of the skin island (p = 0.002), and the number of osteotomies (p = 0.001).Conclusion For the success of FFF, there are many influencing factors. If the mentioned risk factors are considered, the number of osteotomies, size of the skin paddle, and fibula are as small as possible, and a suitable osteosynthesis material is chosen, the FFF is a safe solution for mandibular reconstruction.
Keywords: free vascularized bone transfer; osteocutaneous free fibula flap; mandibular reconstruction